Reduksi Keluhan Muskuloskeletal Pekerja dan Waktu Siklus Prses Produksi Berbasis Ergonomi Pada Insdustri Karet - Setiawan, Heri (Jurnal Rekayasa Sistem Industri, 2015)
Achievement of plant capacity and reducing bottlenecks in the production process at wet blanketworkstation determined on the level worker of musculoskeletal disorders and the cycles time of the productionprocess per slabs. Capabilities and limitations of workers, equipment, task, and environmental organizationsmust be harmonized for level of workers musculoskeletal disorders and the cycles time of the productionprocess per slabs reduction. The problem scale priority based on total ergonomics must be applied early withidentification of 8 aspects of ergonomics, planned and considered systemic, holistic, interdisciplinary andparticipatory and apply the concept of appropriate technology become one of problem solution about this case.Reduction of level of worker musculoskeletal disorders and cycles time of the production process per slabsbased on ergonomics; include redesigning of the ergonomics table and standing-seat chair folding work wetblanket, setting the pattern system of pair work, giving an active break, providing additional nutrition inthe form of sweet tea and snack pempek, provision of personal protective equipment, and redesigning of thephysical work environment. Experimental research was using the treatment by subject design, with involved17 workers samples who perform activities on the conditions of activity before and after the redesign basedon ergonomics. The level worker of muskuluskeletal disorders, and the cycle time of the production processper slabs data were analyzed using Two Pair Sample t-test at a significance level of 5%. The results of studyshowed that after redesign of wet blanket workstation based on ergonomics there was a significant reductionof the level worker of muskuluskeletal disorders as 21.02%, and reduction of the cycles time of the productionprocess per slabs as 21.85%.